The Science of Religion in the Vedic Texts: A Physico-Theological Perspective - Chalise, Keshav Raj (The Outlook: Journal of English Studies, 2021)
Vedas, in common perception, are understood as purely cultural texts even to the academic province with the logic that they provide purely religious and theological knowledge, however the quest of spiritual truth is the prime concern of Vedas. The real problem on such understanding is that the scientific part of the Vedas is always under the shadow. This is partly from the Vedic scholars, as they have not properly revealed the scientific part of the Vedic knowledge; and partly it is the weakness of scientists because they have heavy concentration just on the facts that they have little time to keep eyes on the Vedic science. The question is always unaddressed whether religion has science. This study tries to unearth the part of science veiled within the Vedic texts, especially seeing the Vedic science of ecology, biodiversity, physics and cosmology using physico-theology as the tool of observation.